2021
DOI: 10.3390/genes12101556
|View full text |Cite
|
Sign up to set email alerts
|

RAS Dimers: The Novice Couple at the RAS-ERK Pathway Ball

Abstract: Signals conveyed through the RAS-ERK pathway constitute a pivotal regulatory element in cancer-related cellular processes. Recently, RAS dimerization has been proposed as a key step in the relay of RAS signals, critically contributing to RAF activation. RAS clustering at plasma membrane microdomains and endomembranes facilitates RAS dimerization in response to stimulation, promoting RAF dimerization and subsequent activation. Remarkably, inhibiting RAS dimerization forestalls tumorigenesis in cellular and anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 91 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…Although MAPKs were shown to exert their function at cytoplasmic as well as nuclear cellular compartments ( Figure 1 ), the latter is probably the most widely studied and several functions have been described including regulation of transcription, DNA replication, chromatin remodeling, and miRNA synthesis. Regulatory components, such as scaffold proteins and dimerization were shown to take part in this pathway’s complex regulation by defining frequency, amplitude and intensity of the signal allowing for a wide range of biological outcomes ( Herrero and Crespo, 2021 ). Several reports suggest that ERK nuclear localization depends, among others, on ERK expression levels such that overexpression increases nuclear translocation probability by passive diffusion ( Fukuda et al, 1997 ), and phosphorylation by casein kinase 2 (CK2) that enhances ERK interaction with a nuclear import protein (importin 7) ( Chuderland et al, 2008 ).…”
Section: Upon Extracellular-signal Regulated Kinase Activationmentioning
confidence: 99%
“…Although MAPKs were shown to exert their function at cytoplasmic as well as nuclear cellular compartments ( Figure 1 ), the latter is probably the most widely studied and several functions have been described including regulation of transcription, DNA replication, chromatin remodeling, and miRNA synthesis. Regulatory components, such as scaffold proteins and dimerization were shown to take part in this pathway’s complex regulation by defining frequency, amplitude and intensity of the signal allowing for a wide range of biological outcomes ( Herrero and Crespo, 2021 ). Several reports suggest that ERK nuclear localization depends, among others, on ERK expression levels such that overexpression increases nuclear translocation probability by passive diffusion ( Fukuda et al, 1997 ), and phosphorylation by casein kinase 2 (CK2) that enhances ERK interaction with a nuclear import protein (importin 7) ( Chuderland et al, 2008 ).…”
Section: Upon Extracellular-signal Regulated Kinase Activationmentioning
confidence: 99%
“…This comprises a three-tiered signaling module sequentially linking MAPKKKs of the RAF family serine/threonine kinases (ARAF, BRAF and CRAF); MAPKKs dual-specificity kinases MEK 1 and 2; and MAPKs ERK 1 and 2, in a cascade of serial phosphorylation events, whereby the kinases at the different tiers are consecutively activated. Noticeably, data accumulated over two decades reveal that most of the constituents of the RAS–ERK pathway are capable of forming higher-order assemblies, particularly dimers [ 55 ]. As the last step in the cascade, once phosphorylated/activated, ERKs ultimately convey signals to an ample repertoire of substrates, localized at different subcellular localizations, which eventually translate the biochemical signal into the regulation of key cellular processes such as proliferation, differentiation, survival and motility, in addition to a wide variety of cell-specific activities [ 56 , 57 ].…”
Section: The Ras–erk Pathwaymentioning
confidence: 99%
“…The RAS-ERK pathway exerts a significant function when adjusting pivotal cellular activities, covering proliferation, survival, differentiation, and motility, and is a cascade that translates the extracellular environment into intracellular signaling, encompassing a range of biochemical processes [12,13]. It has been suggested that the biological effects of GTPase activator protein 1 (IQGAP1) on tumor cells can be induced by regulating the response of the RAS signaling pathway [14] and binding to actin is contained in diverse processes like cell binding, propagation, circulate, and transfer [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%